2004
DOI: 10.1677/joe.1.05775
|View full text |Cite
|
Sign up to set email alerts
|

Both estrogen and raloxifene protect against β-amyloid-induced neurotoxicity in estrogen receptor α-transfected PC12 cells by activation of telomerase activity via Akt cascade

Abstract: Although estrogen is known to protect against -amyloid (A )-induced neurotoxicity, the mechanisms responsible for this effect are only beginning to be elucidated. In addition, the effect of raloxifene on A -induced neurotoxicity remains unknown. Here we investigated whether raloxifene exhibits similar neuro-protective effects to estrogen against A -induced neurotoxicity and the mechanism of the effects of these agents in PC12 cells transfected with the full-length human estrogen receptor (ER) gene (PCER). Ralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 44 publications
0
23
1
Order By: Relevance
“…These may be more effective than NGF itself. Estrogen is protective against Aβ in cell lines such as PC12 and human neuronal cells [4,10] but was ineffective on the differentiated cells in this study. The estrogen and NGF may be acting by a similar pathway as both alter phosphotyrosine content in septal neurons over a similar time period [14].…”
Section: Discussioncontrasting
confidence: 48%
“…These may be more effective than NGF itself. Estrogen is protective against Aβ in cell lines such as PC12 and human neuronal cells [4,10] but was ineffective on the differentiated cells in this study. The estrogen and NGF may be acting by a similar pathway as both alter phosphotyrosine content in septal neurons over a similar time period [14].…”
Section: Discussioncontrasting
confidence: 48%
“…Collectively, these effects could explain the reported protective actions of estrogen in AD. It should be mention that the SERM, raloxifene has also been shown to protect against β-amyloid-induced cell death [199], and it has been reported to decrease risk of AD and cognitive impairment in postmenopausal women [206]. As a whole, the above studies support a potential protective role for estrogen in AD, which deserves further study.…”
Section: Gene Mutations Aromatase and Potential Mechanisms Of Estrogenmentioning
confidence: 76%
“…However, a number of studies have shown that estrogen can protect neurons against β-amyloid toxicity [73,185,[195][196][197][198][199], oxidative stress [110][111][112][113]195,200] and excitotoxicity [67,195,201,202], events suggested to participate in the pathology of AD. Additionally, estrogen has been shown to induce dephosphorylation of the tau protein and prevent its hyperphosphorylation in neurons [203].…”
Section: Gene Mutations Aromatase and Potential Mechanisms Of Estrogenmentioning
confidence: 99%
“…Phosphorylation of Akt leads to its activation and protects cells against genomic DNA degradation and membrane PS exposure [45,61,105]. Up-regulation of Akt activity during multiple injury paradigms, such as vascular and cardiomyocyte ischemia [106,107], free radical exposure [45,108], N-methyl-D-aspartate toxicity [109], hypoxia [110,111], β-amyloid toxicity [112][113][114], DNA damage [31, 41,110,115], metabotropic receptor signaling [38,116,117], cell metabolic pathways [42,63], and oxidative stress [31,33,41] increases cell survival. Cytoprotection through Akt also can involve control of inflammatory cell activation [33, 41,61], transcription factor regulation [118], maintenance of mitochondrial membrane potential (ΔΨ m ), prevention of cytochrome c release [45,61,105], and blockade of caspase activity [45,61,110] In addition to targeting the activity of membrane PS exposure and microglial activation, nicotinamide inhibits several pro-inflammatory cytokines, such as interleukin-1β, interleukin-6, interleukin-8, tissue factor, and tumor necrosis factor-α (TNF-α) [119][120][121][122].…”
Section: Innovative Strategies For Neurovascular Protection During Dmmentioning
confidence: 99%